PROMOTING INCLUSIVE EDUCATION THROUGH PHYSICAL EDUCATION: A PEDAGOGICAL PERSPECTIVE - Ferrari , Elena; Luca, Marco De (Academic Journal of Psychology and Education (AJPE), 2025)
Today more than ever, the activation of inclusive projects through the contribution offered by physical education is essential to implement a strong alliance between school and extra-school, between school and family in order to activate a positive contamination of universal and timeless values of motor activities. This becomes essential since the structuring of society requires a cultural and social pact that guarantees in all formal and non-formal environments the learning of skills that could transform children’s lives. It is for this reason that physical activity cannot be for the benefit of a few because the aggregative moments that it can express often become a real lifeline for many young people. In this context, acting through inclusive teaching makes it possible to value and capitalize on the individual differences present in all pupils, with particular attention to situations in which these differences create significant barriers to learning and participation in social life. In fact, for some time now it has ceased to be considered as an access lane only for students with disabilities or special educational needs, qualifying as a quality teaching for all. We can increasingly consider it as a style of teaching, a daily educational and didactic orientation